2020
DOI: 10.1158/0008-5472.can-20-1145
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Epigenetic Landscape in Childhood B Acute Lymphoblastic Leukemia and Its Role in Drug Resistance

Abstract: Although B-cell acute lymphoblastic leukemia (B-ALL) is the most common malignancy in children and while highly curable, it remains a leading cause of cancer-related mortality. The outgrowth of tumor subclones carrying mutations in genes responsible for resistance to therapy has led to a Darwinian model of clonal selection. Previous work has indicated that alterations in the epigenome might contribute to clonal selection, yet the extent to which the chromatin state is altered under the selective pressures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…3e). Interestingly, cancer-related pathways previously identified by RNA-seq or ChIP-seq analysis 5,22 were also found in our compartment-based analysis including Rap1, Ras, Phosphatidylinositol 3-kinase, and calcium signaling. Furthermore, these pathways were shared by at least two of the three cell lines providing evidence that the existence of a core of compacting loci can explain previously described shared phenotypes such as proliferation 5 .…”
Section: Resultssupporting
confidence: 65%
“…3e). Interestingly, cancer-related pathways previously identified by RNA-seq or ChIP-seq analysis 5,22 were also found in our compartment-based analysis including Rap1, Ras, Phosphatidylinositol 3-kinase, and calcium signaling. Furthermore, these pathways were shared by at least two of the three cell lines providing evidence that the existence of a core of compacting loci can explain previously described shared phenotypes such as proliferation 5 .…”
Section: Resultssupporting
confidence: 65%
“…7 We previously demonstrated epigenetically activated MAPK pathway at relapse and a genome-wide shRNA screen-validated MAPK as a driver of clonal evolution and drug resistance. 6,12,16 mutations undetected in some of our WT patients as the lower limit of detection for Sanger sequencing is 15%-20% VAF. In contrast to previous studies with smaller cohorts and specific subtypes of B-ALL, 8,17,18 not all RAS mutated samples in our cohort demonstrated sensitivity to MEKi, but there was a trend toward higher inhibition indexes in mutant cases.…”
Section: Discussionmentioning
confidence: 85%
“…showed enrichment of RAS mutations at relapse from the outgrowth of a small subclone in the diagnostic sample using diagnosis/relapse pairs 7 . We previously demonstrated epigenetically activated MAPK pathway at relapse and a genome‐wide shRNA screen‐validated MAPK as a driver of clonal evolution and drug resistance 6,12,16 . Likewise, Ma et al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Characteristic methylation signatures largely matching the underlying genetic background have been identified and provided basis for DNA methylation-based subtype prediction classifiers, contributing to the clarification of cytogenetically undefined ALL patient groups and facilitating the identification of novel gene fusions [ 90 ]. Some studies suggested that DNA methylation-based biomarkers are not independent predictive markers of patient outcome [ 91 ], while the combined analysis of methylation, DNA-protein interaction, and gene expression in a recent study has uncovered relapse-specific super-enhancers shared by a majority of patients [ 92 ], demonstrating the potential of integrative omic approaches. Large microarray and NGS-based transcriptomic studies identified novel subgroups of ALL patients previously not categorized by more conventional cytogenetic and molecular genetic methods.…”
Section: Genomic Epigenomic and Transcriptomic Background Of Pediatric Leukemiamentioning
confidence: 99%